2010
DOI: 10.2136/sssaj2009.0197
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Calibration of Soil Potassium Availability with Soybean Yield and Trifoliolate Potassium

Abstract: The ability of soil tests to identify nutrient‐deficient soils and recommend fertilizer rates that optimize agronomic yield is essential for profitable soybean [Glycine max (L.) Merr.] production. Our objectives were to correlate relative soybean yield to Mehlich‐3 and 1 mol L−1 HNO3–extractable soil K and trifoliolate‐leaf K concentration at the R1 to R2 development stage and calibrate the K rates for Mehlich‐3‐extractable soil K. Experiments were established on silt loams at 34 site‐years planted with a Matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 17 publications
5
40
2
Order By: Relevance
“…Both the M3 and ASI extraction methods, which are similar to the NH 4 OAc method, have been more readily accepted in recent years as a measure of available soil K because they are convenient in permitting the extraction of other mineral nutrients in one procedure and improve laboratory efficiency. Many studies have shown that available soil K as determined using the ASI and M3 methods is significantly positively correlated to that using the NH 4 OAc method (Loide et al, 2005;Xiong et al, 2007;Slaton et al, 2010). Positive correlations between soil NH 4 OAc-K and ASI-K and M3-K were also observed in our studies (data not shown).…”
Section: Soil K Test Index and K-fertilization Recommendationsupporting
confidence: 84%
“…Both the M3 and ASI extraction methods, which are similar to the NH 4 OAc method, have been more readily accepted in recent years as a measure of available soil K because they are convenient in permitting the extraction of other mineral nutrients in one procedure and improve laboratory efficiency. Many studies have shown that available soil K as determined using the ASI and M3 methods is significantly positively correlated to that using the NH 4 OAc method (Loide et al, 2005;Xiong et al, 2007;Slaton et al, 2010). Positive correlations between soil NH 4 OAc-K and ASI-K and M3-K were also observed in our studies (data not shown).…”
Section: Soil K Test Index and K-fertilization Recommendationsupporting
confidence: 84%
“…The positive correlation between soil NH 4 OAc-K contents and the yield response to K fertilizer have been mentioned in many studies (Mallarino et al 2003;Loide et al 2005;Slaton et al 2010). But the relationship between soil NH 4 OAc-K content and relative yield was weak in our study because of minor response to K fertilization.…”
Section: Discussioncontrasting
confidence: 50%
“…Soybean seed yield can be decreased by more than 50% by K deficiency (Nelson et al, 1946; Jones et al, 1977), but losses of 5 to 20% are more common (Coale and Grove, 1990; Mallarino et al, 1991; Slaton et al, 2010; Clover and Mallarino, 2013). Crop yield loss associated with the physiological effects of K deficiency is partially attributed to reduced assimilate production (Ashley and Goodson, 1972; Sale and Campbell, 1986) and partitioning to the seeds (Ashley and Goodson, 1972; Huber, 1984) due to the reduction in enzymatic activity (Huber, 1984).…”
mentioning
confidence: 99%